ILRI research on animal diseases in Africa—Developing vaccines and diagnostics - Toye, Philip G. (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Phil Toye, reflects on ILRI's vaccine and diagnostics research accomplishments, from the past 10 years, that involved partnerships with other centres and countries in Africa.